PREVALENCE OF PLASMID MEDIATED QNRA, QNRB AND QNRS AMONG CLINICAL ESCHERICHIA COLI ISOLATED FROM URINARY TRACT INFECTIONS IN DUHOK, KURDISTAN REGION OF IRAQ - Ibrahim, Delveen R. (Science Journal of University of Zakho, 2023)
Excessive use of antibiotics (such as fluoroquinolone) and inadequate infection control practices have turned antibiotics resistance (AMR) into a global, public health peril. The current study emphasizes on the prevalence of qnrA, qnrB, and qnrS plasmid in fluroquinolone (FQ) resistant Escherichia coli (E. coli) isolates from urinary tract samples and their correlation with the burden of resistance in these isolates. In this research, several E. coli strains were isolated from outpatients having urinary tract infections (UTIs) from Duhok province, Kurdistan Region of Iraq. Biochemical and Molecular confirmations were performed to confirm the isolates. Antibiotics susceptibility test was performed to detect the isolates antibiogram. Furthermore, polymerase chain reaction (PCR) amplification was used to detect the qnrA, B and S genes. Bioinformatics tools were used to perform the analysis of the results and data visualization. Forty isolates (out of 55) have been confirmed as E. coli. Antibiograms revealed that 70%, 65% and 63% of the isolates were resistant to Ciprofloxacin, Enrofloxacin and Levofloxacin, respectively. While there was variation in resistance to other antibiotics tested. The FQ resistant genes were detected in 17 (42.5%) isolates, with some isolates carrying more than one gene. The variant qnrS was the most predominant, as it has been detected in 14 isolates. The increasing rates of multidrug resistance E. coli isolates from UTIs, including FQ antibiotics, emphasizes the importance of carefully monitoring their use for UTI treatment.